Macropore–matrix mass transfer of reactive solutes quantified by fluorescence imaging - Haas, C. (2020)
The spatial distribution of dye concentrations was visualized and quantified with a fluorescence imaging technique at a pixel resolution length of ∼100 μm. Submillimeter‐scaled distribution maps of adsorbed dye concentrations were derived using the calibrated Freundlich adsorption model. The sorption isotherm predicted that most of the dye was adsorbed to soil. In total, 1,366 μg of dye was transferred through the coated matrix block, of which 1,181 μg was adsorbed to soil. The applicability of the method was validated by comparing applied and recovered Na‐fluorescein masses, which corresponded relatively closely. Although the test of the approach presented here was limited by uncertainties regarding the local distributions of water contents and bulk density, the method could be applied to map two‐dimensional horizontal distributions of dye in an intact soil clod for quantifying macropore–matrix mass transfer of the reactive solute.